Risk Factors for Recurrence of Benign Paroxysmal Positional Vertigo. A Clinical Review - Sfakianaki, Ioanna; Binos, Paris; Karkos, Petros; Dimas, Gregorios; Psillas, George K. (My University, 2021)
Benign paroxysmal positional vertigo (BPPV) is one of the most common peripheral vestibular dysfunctions encountered in clinical practice. Although the treatment of BPPV is relatively successful, many patients develop recurrence after treatment. Our purpose is to evaluate the mean recurrence rate and risk factors of BPPV after treatment. A review of the literature on the risk factors of BPPV recurrence was performed. A thorough search was conducted using electronic databases, namely Pubmed, CINAHL, Academic Search Complete and Scopus for studies published from 2000 to 2020. Thirty studies were included in this review with 13,358 participants. The recurrence rate of BPPV ranged from 13.7% to 48% for studies with follow-up <1 year, and from 13.3% to 65% for studies with follow-up ≥2 years. Pathophysiologic mechanisms and implication of each of the following risk factors in the recurrence of BPPV were described: advanced age, female gender, Meniere’s disease, trauma, osteopenia or osteoporosis, vitamin D deficiency, diabetes mellitus, hypertension, hyperlipidemia, cardiovascular disease, migraine, bilateral/multicanal BPPV, cervical osteoarthrosis and sleep disorders. Patients with hyperlipidemia and hypertension had the highest recurrence rates of BPPV, 67.80% and 55.89%, respectively, indicating that vascular comorbidities increase the risk of BPPV recurrence. In addition, more than half of patients (53.48%) with diabetes mellitus and BPPV experienced recurrence of BPPV. Knowledge and awareness of risk factors for recurrence of BPPV are essential for the assessment and long-term prognosis of patients. Identification of these relapse risk factors may enhance the ability of clinicians to accurately counsel patients regarding BPPV and associated comorbidities.
Keywords: BPPV; BPPV recurrence; Risk factors